Retirement and healthcare utilization - Wolfgang Frimmel; Gerald J. Pruckner (Johannes Kepler University Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2018)
Pension systems and reforms thereof are often discussed in the context of financial viability. In industrialized countries, these debates grow in intensity with the aging of the population; however, an increase in retirement age may create unintended side effects with regards to retiree health or healthcare costs. This study empirically analyzes the effect of (early) retirement on individual inpatient and outpatient healthcare expenditure in Austria. We use comprehensive labor market and retirement data from the Austrian Social Security Database, together with detailed information about individual inpatient and outpatient healthcare service utilization in the province of Upper Austria. To account for endogeneity in retirement decisions, we exploit exogenous variation in the early retirement age as induced by two Austrian pension reforms (i.e., those in 2000 and 2003). We find there to be significant negative effects of retirement on healthcare expenditure. For both genders, retirement reduces subsequent expenditure for outpatient medical attendance and hospitalization. Analyses of disaggregated components of healthcare expenditure confirm a positive health effect caused by physical and emotional relief following retirement. Apart from direct health effects, the results also reveal behavioral changes in the utilization of healthcare services. These changes in health behavior seem particularly relevant among blue-collar workers.
Keywords: I11; I12; J26; H51; 330; retirement; healthcare expenditure; health behavior; instrumental variable